2015
DOI: 10.1007/s00415-015-7876-3
|View full text |Cite
|
Sign up to set email alerts
|

Color vision impairment in multiple sclerosis points to retinal ganglion cell damage

Abstract: Multiple Sclerosis (MS) results in color vision impairment regardless of optic neuritis (ON). The exact location of injury remains undefined. The objective of this study is to identify the region leading to dyschromatopsia in MS patients' NON-eyes. We evaluated Spearman correlations between color vision and measures of different regions in the afferent visual pathway in 106 MS patients. Regions with significant correlations were included in logistic regression models to assess their independent role in dyschro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 25 publications
1
22
1
Order By: Relevance
“…The loss of RGC was recently identified as the ultimate responsible for visual impairment in patients suffering from another neurodegenerative process, multiple sclerosis. 33 Thus, a similar process could be the cause of contrast and color deficiencies in AD individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of RGC was recently identified as the ultimate responsible for visual impairment in patients suffering from another neurodegenerative process, multiple sclerosis. 33 Thus, a similar process could be the cause of contrast and color deficiencies in AD individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found correlations between the thickness of the GCIPL and the RNFL, and visual acuity, especially low contrast visual acuity [14][15][16]. One study also detected a moderate, statistically significant correlation between dyschromatopsia and GCIPL thickness in MS-NON eyes [17].…”
Section: Visual Functionmentioning
confidence: 95%
“…MRI studies have found several associations between RNFL thickness and MRI parameters in MS patients [27][28][29][30]. Furthermore, recent studies have observed correlations between GCIPL thickness and thalamus volume [31], normalized brain parenchymal volume [17], intracranial volume [22], cortical grey matter volume [22], and number and volume of cortical lesions [31]. Additionally, studies have found associations between increased thinning of the GCIPL and T2 lesions [26], increased lesion volume in the optic radiation [32] and development of contrast-enhancing lesions [26,27].…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“… 23 RGC loss (as observed using SD-OCT) was recently identified as the cause of visual impairment in patients suffering from another neurodegenerative process, multiple sclerosis. 24 Thus, a similar process could be the cause of the contrast and colour deficiencies in patients with PD. In addition, in the mammalian retina, colour vision and contrast sensitivity are modulated through D1 and D2 receptors.…”
Section: Discussionmentioning
confidence: 99%